Peningkatan Aktivitas Belajar Siswa dalam Materi Gerak Lurus Melalui Pemberian Pertanyaan Singkat dan Tes Kecil pada Akhir Pembelajaran di Kelas X MIPA 2 SMA Negeri 1 Candung - Asfiarty Amran (Departement of Mathematics Education, 2022)
This study aims to obtain information and discuss about Improving Student Learning Activities in Straight Motion Material Through Giving Short Questions and Small Tests at the End of Learning in Class X MIPA 2 SMA Negeri 1 Cdung. This type of research is classroom action research (CAR). The research location was at CMAN 1 SMAN 1, Agam Regency. The subjects in this study were 21 students of class X MIPA 2 SMA Negeri 1 Candung. The research was carried out in the odd semester of the 2021/2022 school year which began in October 2021. The data collection technique in this study was carried out using instruments, observation sheets and tests. Data analysis techniques use percentage formulas and data reduction. The results showed that by giving short questions and small tests at the end of the learning process which was carried out continuously, it could increase students' activity in learning physics. It can be seen from the changes in student activity in participating in the teaching and learning process, because students know that each activity during learning will have value and at the end of the lesson a small test will be held, so that students are more motivated and concentrate on the lesson during the teaching and learning process